Pengaruh Medan Listrik Terhadap Komponen Elektronik - Amril - - (Jurnal Ilmiah Poli Rekayasa, 2018)
This research reviewed the effect of induction voltage resulting of the electromagnetic induction from the thunderbolt attack to the electronic equipment especially if the induction effect to the component has a high sensitivity rate that was IC CMOS component. In this study the experiments done in the laboratory of High Voltage Technique where the impulse voltage as a simulation to the thunderbolt external voltage surge for the Electronic circuit. Experiment I the distance component of the test article to the test point was 5 cm with the impulse voltage of 99.3 kV, induction voltage 158.41 V, Experiment II with the distance of 7.5 cm, the impulse voltage 88.3 kV so the induction voltage 105.62 V IC, in the experiment III the distance of the test article was 10 cm from the test point. The impulse voltage 88.3 kV and the induction voltage was 79.2 V, In the experiment IV the component distance was 15 cm. the impulse voltage 88.3 kV and the induction voltage as big as 52.74 V.From each experiment IC make damage, where distance component from each experiment settled more distant so component no make damage. From the measurement and calculation yields then the induction voltage resulted will damage the IC component conformed to the yield presented by Hasse in the table 2.1 where the component CMOS 70-100V. Where the study results proved that the electromagnetic induction from indirect thunderbolt attach can result an interference and damage to the electronic component tested, as the distance between the component and the ball gap to the impulse tension was very influential in determining of damaged mechanism of IC in self.